2019
DOI: 10.1038/s41419-019-1978-2
|View full text |Cite
|
Sign up to set email alerts
|

CircERCC2 ameliorated intervertebral disc degeneration by regulating mitophagy and apoptosis through miR-182-5p/SIRT1 axis

Abstract: The molecular mechanism of intervertebral disc degeneration (IVDD) remains unclear. This study aimed to investigate the role of circular RNAs (circRNAs) in the pathogenesis of IVDD. We sued nucleus pulposus (NP) tissues of patients, tert-butyl hydroperoxide (TBHP) stimulated NP cells (NPCs), and IVDD rat model to explore the interaction between circERCC2 and miR-182-5p/SIRT1 axis. The results showed that downregulation of circERCC2 increased the level of miR-182-5p and decreased the level of SIRT1 in degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 58 publications
1
119
0
Order By: Relevance
“…Mitochondrial dysfunction causes cell/organ injury through several mechanisms, including diminished cellular energy status (low cellular ATP level, energy stress) and enhanced production of reactive oxygen species (ROS). Furthermore, mitochondrial damage is associated with the release of several apoptosis-activated factors, leading to programmed cell death [163]. Disturbances in ionic balance, particularly an increase in mitochondrial and cytoplasmic Ca 2+ , stimulates mitochondrial permeability transition (PT) accompanied by the opening of non-selective channels known as the PT pores (PTP) that allow free movement of ions and other solutes with a molecular mass <1.5 kDa across the inner mitochondria membrane (IMM) [4].…”
Section: Mitophagymentioning
confidence: 99%
“…Mitochondrial dysfunction causes cell/organ injury through several mechanisms, including diminished cellular energy status (low cellular ATP level, energy stress) and enhanced production of reactive oxygen species (ROS). Furthermore, mitochondrial damage is associated with the release of several apoptosis-activated factors, leading to programmed cell death [163]. Disturbances in ionic balance, particularly an increase in mitochondrial and cytoplasmic Ca 2+ , stimulates mitochondrial permeability transition (PT) accompanied by the opening of non-selective channels known as the PT pores (PTP) that allow free movement of ions and other solutes with a molecular mass <1.5 kDa across the inner mitochondria membrane (IMM) [4].…”
Section: Mitophagymentioning
confidence: 99%
“…A large of studies shown that the degeneration mainly displays as a large number of the nucleus pulposus cell apoptosis and thus nucleus pulposus cells apoptosis plays a crucial role in IVDD [7,8]. TNF-Ī± is a key proinflammatory cytokine and could induce the apoptosis of nucleus pulposus cells [9]. Thus, TNF-Ī± was commonly administrated as the model of IVDD [10].…”
Section: Introductionmentioning
confidence: 99%
“…SirT1-small interfering (si)rna inhibits nPc apoptosis and senescence. Moreover, this effect is suppressed by circ-ercc2 and mir-182-5p inhibitor, suggesting that circercc2 exerts a protective effect on nPcs that is dependent on mir-182-5p (17).…”
Section: Specificroles Of Circrna In Iddmentioning
confidence: 96%
“…Functional analyses also suggested that circ-ercc2 modulated tert-butyl hydroperoxide-induced nPc apoptosis (through caSP-3, caSP-7 and caSP-9), mitophagy (through PTen-induced kinase 1, parkin, p62, and lc3ii/i) and ecM structure (MMP13 and col2) in vitro and in vivo (17). Fluorescence in situ hybridization and dual-luciferase assays demonstrated that circ-ercc2 could bind to mir-182-5p (17).…”
Section: Specificroles Of Circrna In Iddmentioning
confidence: 97%
See 1 more Smart Citation